A randomised clinical trial of efficacy of melatonin and amitriptyline in migraine prophylaxis of children - Fallah, Razieh; Fazeli Shoroki, Fatemeh; Sekhavat, Leila (Iranian Journal of Child Neurology, 2018)
Objective: No drugs have been approved for pediatric migraine prophylaxis by the Food and Drug Administration up to now. The aim of the present research was to compare effectiveness and tolerability of melatonin and amitriptyline in pediatric migraine prevention. Materials & Methods: In a parallel single-blinded randomized clinical trial, 5-15 year old children with diagnosis of migraine that preventive therapy was indicated in whom and were referred to Pediatric Neurology Clinic of Shahid Sadoughi Medical Sciences University, Yazd-Iran from June 2013 to January 2014, were randomly allocated to receive 1mg/kg amitriptyline or 0.3 mg/kg melatonin for three consecutive months. Primary outcomes were frequency of good response (more than 50 % of reduction in monthly headache frequency) and efficacy in reduction of severity, duration and disability of headache. Secondary outcome was drugs clinical adverse events. Results: 41 girls (51.3%) and 39 boys (48.7%) with mean age of 10.44±2.26 years were evaluated. Good response was seen in 82.5% of amitriptyline and 62%.5 of melatonin groups and amitriptyline was statistically significant more effective. (P= 0.04) Severity, duration and Pediatric Migraine Disability Assessment score (PedMIDAS) of headache reduced with melatonin from 6.05±1.63 to 4.03±1.54 scores, from 2.06±1.18 to 1.41± 0.41 hours, and from 33.13±9.17 to 23.38±9.51 scores, respectively. Severity, duration and PedMIDAS of headache decreased with amitriptyline from 6.41±1.67to 2.25±1.21, from 2.55 ±1.85to 0.56±0.51h, and from 31.4±9.33 to 8.28 ± 3.75, respectively. (All p < 0.05) Both drugs were effective in reduction of monthly frequency, severity, duration and disability of headache. Daily sleepiness was seen in 7.5 % (N=3) of melatonin group as a side effect and adverse events were seen in 22.5% ( N=9) of amitriptyline group including daily sleepiness in four , constipation in three and fatigue in two children and melatonin was safer than amitriptyline (value = 0.04). Conclusions: Amitriptyline and melatonin are effective and safe in pediatric migraine prophylaxis but amitriptyline can be considered as a more effective drug.